Lithium iron phosphate crystal, carbon-coated lithium iron phosphate and preparation method of carbon-coated lithium iron phosphate

Lithium iron phosphate crystals are directly synthesized through liquid phase method, using low temperature heating and no pressurization method, combined with the use of antioxidants and surfactants, the problems of low conductivity and low ion diffusion coefficient of lithium iron phosphate materials are solved, and the nanoification and electrochemical performance are improved.

CN119841295APending Publication Date: 2025-04-18DONGGUAN DONGYANG SOLAR SCI RES & DEV CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411935918.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-26
Publication Date
2025-04-18

AI Technical Summary

Technical Problem

Lithium iron phosphate material itself has defects such as low conductivity, low ion diffusion coefficient, and uneven tap density, which limits its application in lithium-ion batteries.

Method used

Lithium iron phosphate crystals are directly synthesized by liquid phase method, and low-temperature heating and pressure-free methods are used to regulate the morphology and electrochemical properties of the product.

Benefits of technology

Nanoization of lithium iron phosphate crystals is achieved, the specific surface area and electrochemical properties are improved, the migration path of lithium ions is shortened, and the conductive and dynamic properties of the material are enhanced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119841295A_ABST
    Figure CN119841295A_ABST
Patent Text Reader

Abstract

The invention provides a lithium iron phosphate crystal preparation method, which comprises: S1, weighing a soluble phosphorus source, a ferrous iron source and a lithium source, and dissolving in water to obtain a first solution; s2, adding an antioxidant into the first solution to obtain a second solution; s3, Tween 20 is added into the second solution, and a third solution is obtained; s4, adjusting the pH value of the third solution to obtain a fourth solution; and S5, heating the fourth solution to obtain the lithium iron phosphate crystal. According to the method for preparing the lithium iron phosphate crystal, lithium iron phosphate can be directly synthesized in a liquid phase, the requirement for the heating temperature is low, pressurization is not needed, and the synthesis condition of the lithium iron phosphate crystal is simplified.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of preparation of electrochemical energy storage materials, and in particular to a lithium iron phosphate crystal, carbon-coated lithium iron phosphate and a preparation method thereof. Background Art

[0002] With the progress and development of society, people's demand for energy is becoming more and more dependent. Traditional energy represented by coal and oil has become an indispensable part, but a series of environmental problems caused by traditional energy are also gradually aggravating. In recent years, as people's environmental awareness has gradually increased, the development of green energy has received more and more attention, and new energy technologies have been rapidly developed and widely used. As a recyclable green energy, lithium-ion batteries have the advantages of long endurance, high energy density, and high safety. In recent years, they have been widely developed and applied, such as new energy vehicles, digital products, and energy storage fields, which have alleviated the environmental pollution caused by traditional fossil energy for a hundred years and have become the focus of new energy research and development. However, due to the defects of lithium iron phosphate itself, such as low conductivity, low ion diffusion coefficient, and low tap density, its development is restricted. In order to improve the performance of lithium iron phosphate and meet people's use needs, it is necessary to improve the electrochemical properties of lithium iron phosphate by modifying it.

[0003] The most common synthesis methods of lithium iron phosphate include high-temperature solid-phase method and liquid-phase synthesis method. In the common high-temperature solid-phase method, the lithium source, phosphorus source and iron source are mixed in a certain proportion and then calcined under high temperature conditions; this method has a simple process flow and is easy to achieve large-scale production, but the resulting lithium iron phosphate particles have poor morphology consistency, are easy to agglomerate, have poor crystallinity, and have poor electrical properties. The common liquid-phase synthesis method is to synthesize an iron phosphate precursor using alcohol or water as a medium, and then calcine the iron phosphate precursor with a lithium source and a carbon source at high temperature to obtain lithium iron phosphate, or to synthesize lithium iron phosphate using an iron source, a phosphorus source and a lithium source under high temperature and high pressure conditions with an alcohol or aqueous solution as a reaction medium. It needs to be carried out in two steps, or requires high temperature and high pressure, and has high requirements for equipment. Summary of the invention

[0004] The present invention aims to solve at least one of the technical problems in the related art to a certain extent. To this end, the present invention provides a method for preparing lithium iron phosphate crystals by a liquid phase method, which can directly synthesize lithium iron phosphate in a liquid phase, has a low heating temperature requirement, and does not require pressurization, thereby simplifying the synthesis conditions of lithium iron phosphate crystals.

[0005] In one aspect, the present invention provides a method for preparing lithium iron phosphate crystals, comprising the following steps:

[0006] S1: Weigh a soluble phosphorus source, a divalent iron source, and a lithium source, and dissolve them in water to obtain a first solution;

[0007] S2: adding an antioxidant to the first solution to obtain a second solution;

[0008] S3: adding Tween 20 to the second solution to obtain a third solution;

[0009] S4: adjusting the pH of the third solution to obtain a fourth solution;

[0010] S5: heating the fourth solution to obtain the lithium iron phosphate crystals.

[0011] In the present invention, the synthesis conditions of lithium iron phosphate in the liquid phase are simplified, the required reaction temperature is relatively low, and no additional pressurization is required, which reduces the requirements for the reaction container and reduces the synthesis cost. The preparation method of the present invention can well regulate the morphology of lithium iron phosphate crystals to make them uniform in size and regular in morphology, and then control the particle size of the nano-sized lithium iron phosphate positive electrode material in the subsequent calcination and coating, and can shorten the migration path of lithium ions in the electrochemical reaction, thereby improving the electrochemical and kinetic properties of the prepared carbon-coated lithium iron phosphate positive electrode material; at the same time, the specific surface area of ​​the carbon-coated lithium iron phosphate positive electrode material is increased, and the infiltration speed of the material in the battery reaction is improved.

[0012] In the present invention, the above step S1 may further include at least one of the following technical features:

[0013] According to an embodiment of the present invention, the phosphorus source is selected from at least one of diammonium hydrogen phosphate, phosphoric acid, lithium dihydrogen phosphate, ammonium ferrous phosphate, and ammonium dihydrogen phosphate.

[0014] According to an embodiment of the present invention, the divalent iron source is selected from at least one of ferrous sulfate heptahydrate, ferrous sulfate, ferrous nitrate, ferrous oxalate, ferrous acetate and ferrous chloride.

[0015] According to an embodiment of the present invention, the lithium source is selected from at least one of lithium sulfate, lithium carbonate, lithium oxalate, lithium acetate, lithium hydroxide, lithium hydroxide monohydrate, lithium fluoride, and lithium chloride.

[0016] According to an embodiment of the present invention, the element molar ratio of P:Fe:Li is in the range of 1:(1-1.2):(1.1-3.5). The element molar ratio of P:Fe:Li provided by the present invention can be a value of an interval composed of any two values ​​in the above interval, such as 1:1:(1.1-3.5), 1:1.2:(1.1-3.5), 1:(1-1.2):1.1, 1:(1-1.2):3.5, and so on. Exemplarily, the elemental molar ratio of P:Fe:Li is one of 1:1:1.1, 1:1:1.5, 1:1:2.0, 1:1:2.5, 1:1:3.0, 1:1:3.5, 1:1.1:1.1, 1:1.1:1.5, 1:1.1:2.0, 1:1.1:2.5, 1:1.1:3.0, 1:1.1:3.5, 1:1.2:1.1, 1:1.2:1.5, 1:1.2:2.0, 1:1.2:2.5, 1:1.2:3.0, 1:1.2:3.5, or any ratio satisfying the above range of values.

[0017] According to an embodiment of the present invention, in step S1, the amount of water added is not limited, and the phosphorus source, the ferrous iron source, and the lithium source can be completely dissolved. Further, the phosphorus source, the ferrous iron source, and the lithium source are dissolved in water so that the concentration of the P element in the first solution is within the range of 0.8 to 1.2 mol / L. The concentration of the P element in the first solution provided by the present invention can be a value of an interval composed of any two values ​​in the above interval, such as 0.8 to 1.0 mol / L, or 1.0 to 1.2 mol / L, and so on. Exemplarily, the concentration of the P element in the first solution is one of 0.8 mol / L, 0.9 mol / L, 1.0 mol / L, 1.1 mol / L, 1.2 mol / L, or any value that satisfies the above range value.

[0018] According to an embodiment of the present invention, the phosphorus source, the divalent iron source, and the lithium source may be separately configured into solutions and then mixed, or the phosphorus source, the divalent iron source, and the lithium source may be mixed and then configured into a solution.

[0019] In the present invention, the above step S2 may further include at least one of the following technical features:

[0020] According to an embodiment of the present invention, the antioxidant is selected from at least one of ascorbic acid, citric acid, tartaric acid and malic acid.

[0021] According to an embodiment of the present invention, in step S2, the antioxidant concentration of the antioxidant added to the second solution is 1.5 to 2.5 g / L. In the present invention, the antioxidant concentration in the second solution can be a value of an interval composed of any two values ​​in the above interval, such as 1.5 to 2.0 g / L, or 2.0 to 2.5 g / L, and so on. Exemplarily, the antioxidant concentration in the second solution is 1.5 g / L, 1.6 g / L, 1.7 g / L, 1.8 g / L, 1.9 g / L, 2.0 g / L, 2.1 g / L, 2.2 g / L, 2.3 g / L, 2.5 g / L or any value that satisfies the above range value.

[0022] In the present invention, the antioxidant can maintain the reduction potential in the solution, inhibit the oxidation of divalent iron in the solution to generate trivalent iron, reduce the generation of other impurities by the reaction, and improve the purity of the synthetic product.

[0023] In the present invention, the above step S3 may further include at least one of the following technical features:

[0024] According to an embodiment of the present invention, the amount of Tween 20 added is 1% to 5% of the mass of the phosphorus source. The amount of Tween 20 added provided by the present invention can be a value in the interval composed of any two values ​​in the above range, for example, it can be 1% to 3% of the mass of the phosphorus source, or it can be 3% to 5%, and so on. Exemplarily, the amount of Tween 20 added is one of 1%, 2%, 3%, 4%, 5% of the mass of the phosphorus source or any value that satisfies the above range.

[0025] In the present invention, Tween 20 (T20) is a nonionic surfactant having a plurality of hydrophilic groups in its structure and can be adsorbed on the surface of small particles in the liquid phase. The cyclic chain structure in its structure can provide multiple steric hindrance effects, thereby further reducing the surface activation energy of the particles, directionally regulating the specific crystal plane and the particle size, regulating the crystal morphology of the synthetic product in the reaction, increasing the specific surface area of ​​the material, thereby increasing more active sites for electrochemical reactions, shortening the diffusion path of lithium ions, and improving the conductivity of the material.

[0026] According to an embodiment of the present invention, Tween 20 can be directly added to the second solution, or can be added to the second solution after being prepared into a solution.

[0027] In the present invention, the above step S4 may further include at least one of the following technical features:

[0028] According to an embodiment of the present invention, an alkaline solution is added to the third solution to adjust the pH of the third solution.

[0029] According to an embodiment of the present invention, the alkaline solution is at least one of an aqueous ammonia solution, a lithium hydroxide solution, and an ammonium carbonate solution.

[0030] According to an embodiment of the present invention, the pH of the third solution is adjusted to 7.5-10 with an alkaline solution to obtain a fourth solution. In the present invention, the pH of the third solution is adjusted to a value in the interval composed of any two values ​​in the above interval with an alkaline solution, for example, it can be 7.5-8, or 8-10, and so on. Exemplarily, the pH of the third solution is adjusted to one of 7.5, 8.0, 8.5, 9.0, 9.5, 10 or any value that satisfies the above range value with an alkaline solution.

[0031] According to an embodiment of the present invention, step S4 is performed in a protective atmosphere.

[0032] According to an embodiment of the present invention, step S4 is performed in a nitrogen atmosphere or an argon atmosphere.

[0033] In the present invention, the above step S5 may further include at least one of the following technical features:

[0034] According to an embodiment of the present invention, the temperature of the heating treatment is 100°C to 130°C; optionally, the time of the heating treatment is 12h to 24h. The temperature of the heating treatment provided by the present invention can be a value of an interval composed of any two values ​​in the above interval, such as 100°C to 110°C, 110°C to 120°C, 120°C to 130°C, and so on. Exemplarily, the temperature of the heating treatment can be one of 100°C, 105°C, 110°C, 115°C, 120°C, 125°C, 130°C or any value that satisfies the above range value. The time of the heating treatment provided by the present invention can be a value of an interval composed of any two values ​​in the above interval, such as 12h to 16h, 16h to 20h, 20h to 24h, and so on. Exemplarily, the temperature of the heating treatment can be one of 12h, 13h, 14h, 15h, 16h, 17h, 18h, 19h, 20h, 21h, 22h, 23h, 24h or any value that satisfies the above range.

[0035] According to an embodiment of the present invention, step S5 is performed in a protective atmosphere.

[0036] According to an embodiment of the present invention, step S5 is performed in a nitrogen atmosphere or an argon atmosphere.

[0037] According to the embodiment of the present invention, after the heating treatment is completed, post-treatment is required.

[0038] According to an embodiment of the present invention, the post-treatment includes solid-liquid separation, water washing, drying and crushing in sequence, wherein the purpose of the water washing step is to remove soluble impurities.

[0039] According to the embodiment of the present invention, lithium iron phosphate crystals with regular morphology and uniform size are obtained after post-processing.

[0040] The present invention simplifies the synthesis process of lithium iron phosphate in the liquid phase, and does not need to synthesize the iron phosphate precursor in the liquid phase first, and then synthesize the lithium iron phosphate by high-temperature sintering. Compared with the conventional one-step synthesis of lithium iron phosphate, the synthesis method of the present invention requires a lower reaction temperature and does not require additional pressurization. The lithium iron phosphate material can be synthesized under atmospheric pressure, which improves the reaction conditions of high temperature and high pressure required in conventional liquid phase synthesis, reduces the requirements for the reaction container, and reduces the synthesis cost.

[0041] In the present invention, during the liquid phase synthesis process, by adding an appropriate amount of antioxidant and Tween 20 (T20), the morphology of the product lithium iron phosphate can be well regulated, the particles can be refined, the migration path of lithium ions can be shortened, and the electrical properties of the material can be improved. In addition, the antioxidant can also inhibit the oxidation of ferrous ions during the synthesis process, prevent the generation of impurity crystals during the synthesis process, and improve the purity of the product. T20 is a non-ionic surfactant, and there are non-polar hydrophobic groups and polar hydrophilic groups in its molecules, which can inhibit the growth of particles in the reaction and effectively regulate the particle morphology.

[0042] In a second aspect, the present invention provides a method for preparing a carbon-coated lithium iron phosphate positive electrode material, comprising the following steps:

[0043] S6: mixing the carbon source, water and the lithium iron phosphate crystals prepared in step S5 of the first aspect to form a slurry, grinding the slurry, and then spray drying the slurry;

[0044] S7: Sintering the spray-dried powder to obtain the carbon-coated lithium iron phosphate positive electrode material.

[0045] In the present invention, the above step S6 may further include at least one of the following technical features:

[0046] According to an embodiment of the present invention, the solid content of the formed slurry is 32% to 38%. The solid content of the slurry formed by the present invention is a value of an interval composed of any two values ​​in the above interval, such as 32% to 35%, or 35% to 38%, and so on. Exemplarily, the solid content of the formed slurry is one of 32%, 33%, 34%, 35%, 36%, 37%, 38% or any value that satisfies the above range.

[0047] According to an embodiment of the present invention, the grinding process is performed until the slurry D50 is 0.3μm to 2μm. The present invention is ground to the slurry D50 is a value of an interval composed of any two values ​​in the above interval, such as 0.3μm to 1μm, or 1μm to 2μm, and so on. Exemplarily, the slurry is ground to D50 of 0.3μm, 0.4μm, 0.5μm, 0.6μm, 0.7μm, 0.8μm, 0.9μm, 1.0μm, 1.1μm, 1.2μm, 1.3μm, 1.4μm, 1.5μm, 1.6μm, 1.7μm, 1.8μm, 1.9μm, 2.0μm or any value that satisfies the above range.

[0048] According to an embodiment of the present invention, the carbon source is selected from at least one of glucose, sucrose, starch and polyethylene glycol.

[0049] According to an embodiment of the present invention, the amount of the carbon source added is 7% to 13% of the mass of the lithium iron phosphate crystal. The value of the interval composed of any two values ​​in the above interval of the amount of the carbon source added in the present invention, for example, can be 7% to 10% of the mass of the lithium iron phosphate crystal, or 10% to 13%, and so on. Exemplarily, the amount of the carbon source added can be one of 7%, 8%, 9%, 10%, 11%, 12%, 13% of the mass of the lithium iron phosphate crystal or any value that satisfies the above range.

[0050] According to an embodiment of the present invention, the lithium iron phosphate crystals prepared in step S5 of the first aspect are crushed lithium iron phosphate crystals.

[0051] According to an embodiment of the present invention, the feed inlet temperature of the spray drying is 180°C to 240°C, and the discharge port temperature is 105°C to 120°C. The feed inlet temperature of the spray drying of the present invention is a value of the interval composed of any two values ​​in the above interval, for example, it can be 180°C to 200°C, or it can be 200°C to 240°C, and so on. Exemplarily, the feed inlet temperature of the spray drying is one of 180°C, 190°C, 200°C, 210°C, 220°C, 230°C, 240°C, or any value that satisfies the above range value. The discharge port temperature of the spray drying of the present invention is a value of the interval composed of any two values ​​in the above interval, for example, it can be 105°C to 110°C, or it can be 110°C to 120°C, and so on. Exemplarily, the discharge port temperature of the spray drying is one of 105°C, 110°C, 115°C, 120°C, or any value that satisfies the above range value.

[0052] In the present invention, the above step S7 may further include at least one of the following technical features:

[0053] According to an embodiment of the present invention, the sintering process is performed in a protective atmosphere.

[0054] According to an embodiment of the present invention, the protective atmosphere is a nitrogen atmosphere or an argon atmosphere.

[0055] According to an embodiment of the present invention, the temperature of the sintering treatment is 720°C to 800°C. The temperature of the sintering treatment provided by the present invention can be a value of an interval composed of any two values ​​in the above range, such as 720°C to 750°C, 750°C to 770°C, 770°C to 800°C, and so on. Exemplarily, the temperature of the heating treatment can be one of 720°C, 730°C, 740°C, 750°C, 760°C, 770°C, 780°C, 790°C, 800°C or any value that satisfies the above range.

[0056] According to an embodiment of the present invention, the sintering time is 6h to 12h. The sintering time provided by the present invention can be a value of an interval composed of any two values ​​in the above interval, such as 6h to 10h, or 10h to 12h, and so on. Exemplarily, the temperature of the heating treatment can be one of 6h, 7h, 8h, 9h, 10h, 11h, 12h or any value that satisfies the above range.

[0057] According to an embodiment of the present invention, after the sintering is completed, the process further includes cooling to room temperature, crushing, and passing through a 400-mesh sieve to obtain the carbon-coated lithium iron phosphate positive electrode material.

[0058] In the present invention, an organic carbon source such as glucose is used, which is cheap and easy to obtain, and can form a conductive layer on the surface of the lithium iron phosphate crystal, which can not only enhance the conductivity of the carbon-coated lithium iron phosphate positive electrode material, but also restrict particle growth and enhance the conductivity of the carbon-coated lithium iron phosphate positive electrode material. Secondly, the surfactant T20 used in the synthesis of lithium iron phosphate crystals, in the subsequent high-temperature calcination process, the residual T20 decomposes and carbonizes at high temperature, and can also be used as a carbon source for the coating layer.

[0059] In a third aspect, the present invention provides a carbon-coated lithium iron phosphate positive electrode material, wherein the carbon-coated lithium iron phosphate positive electrode material is prepared by the method described in the second aspect.

[0060] Compared with the prior art, the present invention can synthesize lithium iron phosphate directly in the liquid phase by synthesizing lithium iron phosphate crystals in the liquid phase, has low heating temperature requirements, and does not require pressurization, which simplifies the synthesis conditions of lithium iron phosphate crystals; it can realize nano-scale lithium iron phosphate crystals, increase specific surface area, improve uniformity, form regular morphology, reduce particle agglomeration, and form nano-scale carbon-coated lithium iron phosphate positive electrode materials after subsequent calcination, thereby improving electrochemical performance. The carbon-coated lithium iron phosphate positive electrode material prepared by the method of the present invention has good electrical performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0061] Figure 1 This is a SEM image of the lithium iron phosphate crystal obtained in step S5 of Example 1 of the present invention;

[0062] Figure 2 This is a SEM of the carbon-coated lithium iron phosphate positive electrode material obtained in step S7 of Example 1 of the present invention;

[0063] Figure 3 This is a SEM of the lithium iron phosphate crystal obtained in step S4 of comparative example 1 of the present invention;

[0064] Figure 4 This is a SEM of lithium iron phosphate crystals obtained in step S5 of comparative example 3 of the present invention.

[0065] Figure 5 The electrical properties of the carbon-coated lithium iron phosphate positive electrode materials obtained in the comparative example and the example of the present invention are compared. DETAILED DESCRIPTION

[0066] The embodiments of the present invention are described in detail below. Unless otherwise specified, all scientific and technological terms used in the present invention have the same meaning as those generally understood by those skilled in the art to which the present invention belongs. All patents and publications to which the present invention relates are incorporated herein by reference in their entirety. The term "comprising" or "including" is an open expression, i.e., including the contents specified in the present invention, but does not exclude the contents of other aspects.

[0067] According to the embodiment provided by the present invention, the present invention particularly provides a method for preparing lithium iron phosphate crystals, comprising the following steps:

[0068] S1: weighing a soluble phosphorus source, a divalent iron source, and a lithium source according to the element molar ratio of P:Fe:Li being 1:(1-1.2):(1.1-3.5), and dissolving them in water to obtain a first solution; wherein the concentration of the P element in the first solution is in the range of 0.8-1.2 mol / L;

[0069] S2: adding an antioxidant to the first solution to obtain a second solution; wherein the concentration of the antioxidant in the obtained second solution is 1.5 to 2.5 g / L;

[0070] S3: adding Tween 20 to the second solution to obtain a third solution; wherein the amount of Tween 20 added is 1% to 5% of the mass of the phosphorus source;

[0071] S4: adding an alkaline solution to the third solution to adjust the pH of the third solution to 7.5-10, to obtain a fourth solution;

[0072] S5: The fourth solution is heated at 100° C. to 130° C. for 12 h to 24 h. After the reaction is completed, the solution is solid-liquid separated, washed with water, dried, and crushed to obtain the lithium iron phosphate crystals.

[0073] Furthermore, the present invention provides a method for preparing carbon-coated lithium iron phosphate, comprising the following steps:

[0074] S6: Weigh a carbon source according to 7% to 13% of the mass of the lithium iron phosphate crystals, mix the carbon source, water and the lithium iron phosphate crystals prepared in step S5 to form a slurry with a solid content of 32% to 38%, grind the slurry until D50 is 0.3μm to 2μm, and then spray dry; wherein the feed port temperature is 180℃ to 240℃, and the discharge port temperature is 105℃ to 120℃.

[0075] S7: Under a protective atmosphere, the spray-dried powder is sintered at 720° C. to 800° C. for 6 h to 12 h. After sintering, the powder is cooled to room temperature, crushed, and sieved through a 400-mesh sieve to obtain the carbon-coated lithium iron phosphate positive electrode material.

[0076] The embodiments of the present invention will be described in detail below in conjunction with the examples, but it will be appreciated by those skilled in the art that the following examples are only used to illustrate the present invention and should not be considered as limiting the scope of the present invention. In the examples, if no specific conditions are specified, the conditions described in the specification or the conventional conditions or the conditions recommended by the manufacturer are followed. If the manufacturer is not specified for the reagents or instruments used, they are all conventional products that can be purchased commercially.

[0077] Example 1

[0078] S1: Weigh phosphoric acid, ferrous sulfate heptahydrate, and lithium carbonate according to a P:Fe:Li molar ratio of 1:1.1:3.3; prepare a solution so that the phosphoric acid concentration is 0.8 mol / L; and obtain a first solution.

[0079] S2: Add ascorbic acid to the first solution so that the concentration of ascorbic acid is 2 g / L to obtain a second solution.

[0080] S3: Prepare another T20 aqueous solution, add the T20 aqueous solution into the second solution so that the content of T20 is 1.5% of the mass of the phosphorus source, and obtain a third solution.

[0081] S4: Under a nitrogen atmosphere, slowly drop 25% ammonia water into the third solution until the pH value stabilizes at 8.5, to obtain a fourth solution.

[0082] S5: In a nitrogen atmosphere, the fourth solution was heated to 120°C for 12 hours to obtain an off-white product; solid-liquid separation was performed, and the product was repeatedly washed with deionized water to remove soluble impurities. The product was dried and crushed to obtain lithium iron phosphate crystals with regular morphology and uniform size, as shown in the SEM image. Figure 1 shown.

[0083] S6: Glucose is weighed according to 9% of the mass of lithium iron phosphate crystals, and water, glucose and lithium iron phosphate crystals prepared in step S5 are mixed to form a slurry with a solid content of 35%. The slurry is ground until D50 reaches less than 1 μm, and then spray-dried. The feed inlet temperature is 210°C and the discharge outlet temperature is 110°C.

[0084] S7: The spray-dried powder was sintered in a nitrogen atmosphere at a sintering temperature of 735°C for 8 hours. After sintering, the powder was cooled to room temperature, crushed, and sieved through a 400-mesh sieve to obtain the target product, carbon-coated lithium iron phosphate positive electrode material, as shown in the SEM image. Figure 2 shown.

[0085] Example 2

[0086] S1: Weigh diammonium hydrogen phosphate, ferrous nitrate, and lithium sulfate according to a P:Fe:Li molar ratio of 1:1.1:3.3; prepare a solution so that the concentration of diammonium hydrogen phosphate is 0.8 mol / L; and obtain a first solution.

[0087] S2: Add ascorbic acid to the first solution to make the concentration of ascorbic acid 2.5 g / L to obtain a second solution.

[0088] S3: Prepare another T20 aqueous solution, add the T20 aqueous solution into the second solution so that the content of T20 is 3% of the mass of the phosphorus source, and obtain a third solution.

[0089] S4: Under a nitrogen atmosphere, slowly drop 25% ammonia water into the third solution until the pH value stabilizes at 8.5, to obtain a fourth solution.

[0090] S5: Under a nitrogen atmosphere, the fourth solution is heated to 120°C for reaction for 12 hours to obtain an off-white product; the solid-liquid separation is performed, and the product is repeatedly washed with deionized water to remove soluble impurities. The product is dried and crushed to obtain lithium iron phosphate crystals with regular morphology and uniform size.

[0091] S6: Glucose is weighed according to 11% of the mass of lithium iron phosphate crystals, and water, glucose and lithium iron phosphate crystals prepared in step S5 are mixed to form a slurry with a solid content of 35%. The slurry is ground until D50 reaches less than 1 μm, and then spray-dried. The feed inlet temperature is 210°C and the discharge port temperature is 110°C.

[0092] S7: The spray-dried powder is sintered in a nitrogen atmosphere at a sintering temperature of 770°C for 8 hours. After sintering, the powder is cooled to room temperature, crushed, and sieved through a 400-mesh sieve to obtain the target product, carbon-coated lithium iron phosphate positive electrode material.

[0093] Example 3

[0094] S1: Weigh ammonium dihydrogen phosphate, ferrous chloride, and lithium chloride according to a P:Fe:Li molar ratio of 1:1.05:3.15; prepare a solution so that the concentration of ammonium dihydrogen phosphate is 1 mol / L; and obtain a first solution.

[0095] S2: Add ascorbic acid to the first solution so that the concentration of ascorbic acid is 2 g / L to obtain a second solution.

[0096] S3: Prepare another T20 aqueous solution, add the T20 aqueous solution into the second solution so that the content of T20 is 2% of the mass of the phosphorus source, and obtain a third solution.

[0097] S4: Under a nitrogen atmosphere, slowly drop 25% ammonia water into the third solution until the pH value stabilizes at 9, thereby obtaining a fourth solution.

[0098] S5: Under a nitrogen atmosphere, the fourth solution is heated to 120°C for reaction for 12 hours to obtain an off-white product; the solid-liquid separation is performed, and the product is repeatedly washed with deionized water to remove soluble impurities. The product is dried and crushed to obtain lithium iron phosphate crystals with regular morphology and uniform size.

[0099] S6: Glucose is weighed according to 10% of the mass of the lithium iron phosphate crystals, and water, glucose and the lithium iron phosphate crystals prepared in step S5 are mixed to form a slurry with a solid content of 36%. The slurry is ground until D50 reaches less than 1 μm, and then spray-dried. The feed inlet temperature is 210°C and the discharge outlet temperature is 110°C.

[0100] S7: The spray-dried powder is sintered in a nitrogen atmosphere at a sintering temperature of 760°C for 12 hours. After sintering, the powder is cooled to room temperature, crushed, and sieved through a 400-mesh sieve to obtain the target product, carbon-coated lithium iron phosphate positive electrode material.

[0101] Comparative Example 1

[0102] S1: Weigh phosphoric acid, ferrous sulfate heptahydrate, and lithium carbonate according to a P:Fe:Li molar ratio of 1:1.1:3.3; prepare a solution so that the phosphoric acid concentration is 0.8 mol / L; and obtain a first solution.

[0103] S2: Add ascorbic acid to the first solution so that the concentration of ascorbic acid is 2 g / L to obtain a second solution.

[0104] S3: Under a nitrogen atmosphere, slowly drop 25% ammonia water into the second solution until the pH value stabilizes at 8.5 to obtain a third solution.

[0105] S4: In a nitrogen atmosphere, the third solution was heated to 120°C for 12 hours to obtain an off-white product; solid-liquid separation was performed, and the product was repeatedly washed with deionized water to remove soluble impurities on the surface of the product. After drying and crushing, flaky lithium iron phosphate crystals were obtained, and their SEM images were as shown below: Figure 3 shown.

[0106] S5: Weigh a certain mass of water, weigh glucose according to 9% of the mass of the lithium iron phosphate crystals, mix the water, glucose and the lithium iron phosphate crystals prepared in step S4 to form a slurry with a solid content of 35%, grind until D50 reaches less than 1 μm, and then spray dry. The feed inlet temperature is 210°C and the discharge port temperature is 110°C.

[0107] S6: The spray-dried powder is sintered in a nitrogen atmosphere at a sintering temperature of 735°C for 8 hours. After sintering, the powder is cooled to room temperature, crushed, and sieved through a 400-mesh sieve to obtain the target product, carbon-coated lithium iron phosphate positive electrode material.

[0108] Comparative Example 2

[0109] S1: Weigh phosphoric acid, ferrous sulfate heptahydrate, and lithium carbonate according to a P:Fe:Li molar ratio of 1:1.1:3.3; prepare a solution so that the phosphoric acid concentration is 0.8 mol / L; and obtain a first solution.

[0110] S2: Add ascorbic acid to the first solution so that the concentration of ascorbic acid is 2 g / L to obtain a second solution.

[0111] S3: adding a cetyltrimethylammonium bromide (CTAB) aqueous solution into the second solution so that the content of CTAB is 1.5% of the mass of the phosphorus source, to obtain a third solution.

[0112] S4: Under a nitrogen atmosphere, slowly drop 25% ammonia water into the third solution until the pH value stabilizes at 8.5, to obtain a fourth solution.

[0113] S5: In a nitrogen atmosphere, the fourth solution was stirred and heated to 120° C. for 12 h. Since CTAB produced a large number of bubbles during the reaction, the product adhered and condensed on the surface of the container, resulting in the failure of the experimental synthesis.

[0114] Comparative Example 3

[0115] S1: Weigh phosphoric acid, ferrous sulfate heptahydrate, and lithium carbonate according to a P:Fe:Li molar ratio of 1:1.1:3.3; prepare a solution so that the phosphoric acid concentration is 0.8 mol / L; and obtain a first solution.

[0116] S2: Add ascorbic acid to the first solution so that the concentration of ascorbic acid is 2 g / L to obtain a second solution.

[0117] S3: Prepare another T20 aqueous solution, add the T20 aqueous solution into the second solution so that the content of T20 is 6% of the mass of the phosphorus source, and obtain a third solution.

[0118] S4: Under a nitrogen atmosphere, slowly drop 25% ammonia water into the third solution until the pH value stabilizes at 8.5, to obtain a fourth solution.

[0119] S5: In a nitrogen atmosphere, the fourth solution was stirred and heated to 120°C for 12 hours to obtain a gray product; solid-liquid separation was performed, and deionized water was used to wash the product repeatedly to remove soluble impurities on the surface of the product. After drying and crushing, lithium iron phosphate crystals were obtained, and the SEM of the product was as follows: Figure 4 shown.

[0120] S6: Glucose is weighed according to 9% of the mass of lithium iron phosphate crystals, and water, glucose and lithium iron phosphate crystals prepared in step S5 are mixed to form a slurry with a solid content of 35%. The slurry is ground until D50 reaches less than 1 μm, and then spray-dried. The feed inlet temperature is 210°C and the discharge outlet temperature is 110°C.

[0121] S7: The spray-dried powder is sintered in a nitrogen atmosphere at a sintering temperature of 735°C for 8 hours. After sintering, the powder is cooled to room temperature, crushed, and sieved through a 400-mesh sieve to obtain the target product, carbon-coated lithium iron phosphate positive electrode material.

[0122] Performance Test:

[0123] The positive electrode material, conductive agent and PVDF are mixed in the ratio of 92%, 4% and 4%, and an appropriate amount of NMP is added to form a slurry. The slurry is coated on the surface of the aluminum foil, and then dried, cut, weighed and assembled. The charge and discharge test of the button battery is carried out using the Xinwei test cabinet. The test voltage is 3.75V-2V and the ratio is 0.1C-1C. The performance of the above materials is compared based on the test results.

[0124] Table 1: Test results of embodiments and comparative examples

[0125]

[0126]

[0127] Depend on Figure 1 It can be seen that after adding an appropriate amount of T20, the morphology of the lithium iron phosphate crystals synthesized in the liquid phase is regular and uniform. After the morphology of the crystals is regulated and carbon-coated, the particle size of the carbon-coated lithium iron phosphate positive electrode material obtained by calcination reaches the nanometer level. The material morphology is as follows Figure 2 shown.

[0128] Depend on Figure 3 It can be seen that the lithium iron phosphate crystal morphology without the addition of surfactant T20 is irregular, the carbon-coated lithium iron phosphate positive electrode material obtained by subsequent calcination is easy to agglomerate, and its electrical performance is also poor.

[0129] Depend on Figure 4 It can be seen that excessive addition of surfactant T20 causes T20 to coat the surface of lithium iron phosphate crystals during the reaction, which enhances the adsorption force between particles and increases the thickness of the surface layer, but reduces the ability to control the morphology. The morphology of the synthesized lithium iron phosphate crystals is as follows: Figure 4 As shown, the increase in material particle size makes lithium ion transmission more difficult and further affects its electrical performance.

[0130] From Table 1 and Figure 5 It can be seen that not adding or adding excessive T20 will lead to a decrease in the capacity of the synthesized carbon-coated lithium iron phosphate.

[0131] In the description of this specification, the description with reference to the terms "some embodiments", "other embodiments", "embodiment", "example", etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representations of the above terms do not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described may be combined in any one or more embodiments or examples in a suitable manner. In addition, those skilled in the art may combine and combine the different embodiments or examples described in this specification and the features of the different embodiments or examples, unless they are contradictory.

[0132] Although the embodiments and examples of the present invention have been shown and described above, it is to be understood that the above embodiments and examples are exemplary and are not to be construed as limitations of the present invention. A person skilled in the art may change, modify, replace and modify the above embodiments and examples within the scope of the present invention.

Claims

1. A method for preparing lithium iron phosphate crystals, characterized in that: The following steps are involved: S1: Weigh a soluble phosphorus source, a divalent iron source, and a lithium source, and dissolve them in water to obtain a first solution; S2: adding an antioxidant to the first solution to obtain a second solution; S3: adding Tween 20 to the second solution to obtain a third solution; S4: adjusting the pH of the third solution to obtain a fourth solution; S5: heating the fourth solution to obtain the lithium iron phosphate crystals.

2. The preparation method according to claim 1, characterized in that: In step S1, the phosphorus source is selected from at least one of diammonium hydrogen phosphate, phosphoric acid, lithium dihydrogen phosphate, ammonium ferrous phosphate, and ammonium dihydrogen phosphate; Optionally, the ferrous iron source is selected from at least one of ferrous sulfate heptahydrate, ferrous sulfate, ferrous nitrate, ferrous oxalate, ferrous acetate, and ferrous chloride; Optionally, the lithium source is selected from at least one of lithium sulfate, lithium carbonate, lithium oxalate, lithium acetate, lithium hydroxide, lithium hydroxide monohydrate, lithium fluoride, and lithium chloride; Optionally, the element molar ratio of P:Fe:Li is 1:(1-1.2):(1.1-3.5).

3. The preparation method according to claim 1, characterized in that: In step S2, the antioxidant is selected from at least one of ascorbic acid, citric acid, tartaric acid, and malic acid; Optionally, in step S2, the antioxidant is added to the second solution at a concentration of 1.5 to 2.5 g / L.

4. The preparation method according to claim 1, characterized in that: In step S3, the amount of Tween 20 added is 1% to 5% of the mass of the phosphorus source.

5. The preparation method according to claim 1, characterized in that: In step S4, an alkaline solution is added to the third solution to adjust the pH of the third solution; Optionally, the alkaline solution is at least one of an aqueous ammonia solution, a lithium hydroxide solution, and an ammonium carbonate solution; Optionally, the pH of the third solution is adjusted to 7.5-10 with an alkaline solution to obtain a fourth solution.

6. The preparation method according to claim 1, characterized in that: In step S5, the temperature of the heating treatment is 100° C. to 130° C.; optionally, the time of the heating treatment is 12 h to 24 h.

7. A method for preparing a carbon-coated lithium iron phosphate positive electrode material, characterized in that: The following steps are involved: S6: mixing a carbon source, water and the lithium iron phosphate crystals prepared in step S5 according to any one of claims 1 to 6 to form a slurry, grinding the slurry, and then spray drying the slurry; S7: Sintering the spray-dried powder to obtain the carbon-coated lithium iron phosphate positive electrode material.

8. The preparation method according to claim 7, characterized in that: In step S6, grinding is performed until the slurry D50 is 0.3 μm to 2 μm; Optionally, the carbon source is selected from at least one of glucose, sucrose, starch, and polyethylene glycol; Optionally, the added amount of the carbon source is 7% to 13% of the mass of the lithium iron phosphate crystals.

9. The preparation method according to claim 7, characterized in that: In step S7, the sintering process is performed in a protective atmosphere; Preferably, the protective atmosphere is a nitrogen atmosphere or an argon atmosphere; Optionally, the sintering temperature is 720°C to 800°C; Optionally, the sintering treatment time is 6 hours to 12 hours.

10. A carbon-coated lithium iron phosphate positive electrode material, characterized in that: The carbon-coated lithium iron phosphate positive electrode material is prepared by the method according to any one of claims 7 to 8.